The synergistic response of primary production in grasslands to combined nitrogen and phosphorus addition is caused by increased nutrient uptake and retention - Eduardo Vázquez; Elizabeth T. Borer; Miguel N. Bugalho; Maria C. Caldeira; Rebecca L. McCulley; Anita C. Risch; Eric W. Seabloom; George R. Wheeler; Marie Spohn (Plant and Soil, 2023)
Background and aims A synergistic response of aboveground plant biomass production to combined nitrogen (N) and phosphorus (P) addition has been observed in many ecosystems, but the underlying mechanisms and their relative importance are not well known. We aimed at evaluating several mechanisms that could potentially cause the synergistic growth response, such as changes in plant biomass allocation, increased N and P uptake by plants, and enhanced ecosystem nutrient retention. Methods We studied five grasslands located in Europe and the USA that are subjected to an element addition experiment composed of four treatments: control (no element addition), N addition, P addition, combined NP addition. Results Combined NP addition increased the total plant N stocks by 1.47 times compared to the N treatment, while total plant P stocks were 1.62 times higher in NP than in single P addition. Further, higher N uptake by plants in response to combined NP addition was associated with reduced N losses from the soil (evaluated based on soil δ 15 N) compared to N addition alone, indicating a higher ecosystem N retention. In contrast, the synergistic growth response was not associated with significant changes in plant resource allocation. Conclusions Our results demonstrate that the commonly observed synergistic effect of NP addition on aboveground biomass production in grasslands is caused by enhanced N uptake compared to single N addition, and increased P uptake compared to single P addition, which is associated with a higher N and P retention in the ecosystem.

Differential regulation of extracellular matrix proteins in three recurrent liver metastases of a single patient with colorectal cancer - Hannah Voß; Marcus Wurlitzer; Daniel J. Smit; Florian Ewald; Malik Alawi; Michael Spohn; Daniela Indenbirken; Maryam Omidi; Kerstin David; Hartmut Juhl; Ronald Simon; Guido Sauter; et al. (Clinical & Experimental Metastasis, 2020)
Colorectal cancer (CRC) patients suffer from the second highest mortality among all cancer entities. In half of all CRC patients, colorectal cancer liver metastases (CRLM) can be observed. Metastatic colorectal cancer is associated with poor overall survival and limited treatment options. Even after successful surgical resection of the primary tumor, metachronous liver metastases occur in one out of eight cases. The only available curative intended treatment is hepatic resection, but metachronous CRLM frequently recur after approximately 1 year. In this study, we performed a proteome analysis of three recurrent liver metastases of a single CRC patient by mass spectrometry. Despite surgical resection of the primary CRC and adjuvant chemotherapy plus cetuximab treatment, the patient developed three metachronous CRLM which occurred consecutively after 9, 21 and 31 months. We identified a set of 1132 proteins expressed in the three metachronous CRLM, of which 481 were differentially regulated, including 81 proteins that were associated with the extracellular matrix (ECM). 56 ECM associated proteins were identified as upregulated in the third metastasis, 26 (46%) of which were previously described as negative prognostic markers in CRC, including tenascin C, nidogen 1, fibulin 1 and vitronectin. These data may reflect an ascending trend of malignancy from the first to the third metachronous colorectal cancer liver metastasis. Additionally, the results indicate different ECM phenotypes for recurrent metachronous metastasis, associated with different grades of malignancy and highlights the importance of individual analysis of molecular features in different, consecutive metastatic events in a single patient.

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Fine mapping of HIV-1 Nef-epitopes by monoclonal antibodies - H. Siakkou; S. Jahn; N. Kienzle; R. Ulrich; C. Grtzinger; T. Schneider; B. Kohleisen; G. Pauli; R. Spohn; G. Jung; N. Mller-Lantzsch; D. H. Krger (Archives of Virology, 1993)